The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/drones6070179
|View full text |Cite
|
Sign up to set email alerts
|

Urban Air Mobility: Systematic Review of Scientific Publications and Regulations for Vertiport Design and Operations

Abstract: Novel electric aircraft designs coupled with intense efforts from academia, government and industry led to a paradigm shift in urban transportation by introducing UAM. While UAM promises to introduce a new mode of transport, it depends on ground infrastructure to operate safely and efficiently in a highly constrained urban environment. Due to its novelty, the research of UAM ground infrastructure is widely scattered. Therefore, this paper selects, categorizes and summarizes existing literature in a systematic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 85 publications
0
7
0
Order By: Relevance
“…Since the vertiport describes a significant bottleneck especially for near-term UAM applications, a vertiport's performance, operational capability and resilience are of great interest. In HorizonUAM, the vertiport is being examined in terms of regulatory and operational state of the art [60], exemplary layout designs and corresponding concept of operations for both low-and high-density throughput scenarios [61], performance-based rating of a vertiport's airside operation [62] and a vertiport's placement inside airport environment [57]. Furthermore, a vertiport network in an urban environment was developed and compared to ground-based traffic networks [37] and the development and validation of real vertiport prototypes and their operation inside a scaled urban environment suitable for flight testing [63] is envisaged.…”
Section: Building a "U-space Regulatory Sandbox"mentioning
confidence: 99%
“…Since the vertiport describes a significant bottleneck especially for near-term UAM applications, a vertiport's performance, operational capability and resilience are of great interest. In HorizonUAM, the vertiport is being examined in terms of regulatory and operational state of the art [60], exemplary layout designs and corresponding concept of operations for both low-and high-density throughput scenarios [61], performance-based rating of a vertiport's airside operation [62] and a vertiport's placement inside airport environment [57]. Furthermore, a vertiport network in an urban environment was developed and compared to ground-based traffic networks [37] and the development and validation of real vertiport prototypes and their operation inside a scaled urban environment suitable for flight testing [63] is envisaged.…”
Section: Building a "U-space Regulatory Sandbox"mentioning
confidence: 99%
“…In a literature review of urban air mobility (UAM) developments, Garrow et al (2021) identified a need for route optimization algorithms [18]. Another literature review by Schweiger and Preis (2022) affirmed that airspace management and traffic separation principles were critical considerations for UAM development [19]. The study suggested that AAM routes follow arterial highway systems into and out of major cities.…”
Section: Traffic Managementmentioning
confidence: 99%
“…however, there is a lack of access from an ATC perspective, such as approach control, which occurs around the vertiport. In July 2022, an interesting review paper [34] was published covering discussions between various industries and academia regarding the design and operation of vertiports. In the study, it was mentioned that the initial uncertainty about the name of UAM ground infrastructure was overcome, but studies related to vertiports still tend to describe a vision more than providing a realistic and implementable proposal.…”
Section: Related Work and Previous Researchmentioning
confidence: 99%